BARRIERS TO CERVICAL CANCER SCREENING IN RIAU ISLANDS PROVINCE INDONESIA - Yanti, Wa Ode Rosni (Indonesia Epidemiological Journal, 2023)
Background: Cervical cancer is the most common reproductive health cancer in Riau Islands. In most cases, women report to health when diseases in its advanced stage. In this study, the service provider’s perceptions about barriers for women to access cervical cancer screening in Riau Islands Province was investigated.Methods: This was a qualitative study using in-depth interviews and focus group discussion to obtain data with 7 districts coordinators and 45 service providers of cervical cancer screening in public health centers in 7 districts in Riau Islands Province. The study was conducted in June – July 2021. Program data, monthly and annual report from the Provincial Cancer Control Program were analyzed to identify the health facilities which were providing cervical cancer screening. Results: Almost all respondents reported that the delivery and uptake of cervical cancer screening was compromised because of factors such as gross shortage of staff andthe lack of supportive supervision. In addition, the lack of awareness of the disease, feeling embarrassment and anxiety about the procedure of the screening among community members.Conclusion: A number of factors that are barriers to cervical cancer screening. There is a need to continue creating awareness among community members and also addressing barriers such as shortage of staff. The service providers must be aware cultural barriers and should reach out community resources to alleviate these barriers. Culturally responsive communication, making faith-based groups a community resource target, social support and networking can improve screening rates.